The Impacts of Woodchip Co-Firing on Boiler Efficiency and the Environment at the 100 MW CFB Sebalang Power Plant as a Green Energy Enhancement - Burhanuddin Amrulloh; Prabowo Prabowo; Benny Susanto (Green Publisher Indonesia, 2026)
Biomass co-firing in coal-fired power plants is one of the energy transition strategies that enables the utilization of existing power generation assets. This study evaluates the effects of woodchip co-firing on the circulating fluidized bed (CFB) boiler at PLTU Sebalang Unit 1 (2 × 100 MW) using woodchip co-firing ratios of 0%, 10%, 20%, and 30%. The parameters analyzed included gross load, gross and net energy production, fuel consumption across the four coal feeders, total fuel consumption, specific fuel consumption (SFC), gross calorific value (GCV), gross plant heat rate (GPHR), and net plant heat rate (NPHR). The results showed that increasing the woodchip co-firing ratio to 30% did not significantly reduce the gross load, which decreased only from 87.11 MW to 86.94 MW (approximately 0.20%). However, total fuel consumption increased from 267.06 tons to 328.50 tons, while SFC rose from 0.678 kg/kWh to 0.840 kg/kWh. The GPHR increased from 3,044.08 kcal/kWh to 3,448.24 kcal/kWh at a 30% woodchip co-firing ratio, whereas the NPHR increased from 3,369.01 kcal/kWh to 3,830.29 kcal/kWh. These findings suggest that woodchip co-firing can maintain load stability but results in higher fuel consumption and heat rate penalties because of the lower calorific value of woodchips, their potentially higher moisture content, and challenges associated with fuel homogenization and feeding. Therefore, implementing medium- to high-ratio woodchip co-firing requires stringent woodchip quality control, feeder calibration, combustion air optimization, and continuous heat rate monitoring based on actual operating data.